Design and simulation study of ultra-fast beam bunches split for three orthogonal planes high-energy electron dynamic radiography. (14th September 2017) - Zhao, Q.T.; Cao, S.C.; Shen, X.K.; Wang, Y.R.; Zong, Y.; Xiao, J.H.; Zhu, Y.L.; Zhou, Y.W.; Liu, M.; Cheng, R.; Zhao, Y.T.; Zhang, Z.M.; et al.
Abstract: Here a compact three orthogonal planes high-energy electron radiography system was proposed. One of the critical technologies, the ultra-fast beam bunches split from the bunch train are studied. The separated bunches could be transported to the three orthogonal planes of the target for dynamic radiography diagnostics. The key elements of the ultra-fast bunches split system are transverse deflecting cavity (TDC) and the twin septum magnet (TSM). The principle of TDC and TSM are briefly introduced. An example of the beam bunches split system for test experiment (40 MeV electron beam) with TDC and TSM is designed and studied by particle-tracking simulation and it confirms this method is valid and feasible. Especially with TSM, a compact three orthogonal planes radiography system can be realized. The evolution of the beam parameters along the beam line from simulation are investigated. The detailed design of the beam split system and beam dynamics simulation study are presented in this paper.